2017
DOI: 10.20944/preprints201705.0111.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lévy Statistics and Glassy Behavior of Light in Random Fiber Lasers

Abstract: Abstract:The interest in random fiber lasers (RFLs), first demonstrated one decade ago, is still growing and their basic characteristics have been studied by several authors. RFLs are open systems that present instabilities in the intensity fluctuations due to the energy exchange among their non-orthogonal quasi-modes. In this work, we present a review of the recent investigations on the output characteristics of a continuous-wave erbium-doped RFL, with emphasis on the statistical behavior of the emitted inten… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
(150 reference statements)
0
2
0
Order By: Relevance
“…Due to the interesting characteristics that RLs present for the investigation of new optical phenomena and applications, various studies have been carried out to find new materials or mechanisms that optimize their performance and efficiency. Actually, the most used strategy consists of managing the scattering strength, for example, from the variation in the scattering particle density, or the excitation volume of the RL medium. This experimental procedure can also be used to tune the spatial coherence of RLs. , In a different approach, we recently demonstrated that by introducing a degree of randomness on the intensity distribution of the spatial light pattern that pumps a random lasing medium, it is possible to control and improve the RL efficiency by more than 1 order of magnitude .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the interesting characteristics that RLs present for the investigation of new optical phenomena and applications, various studies have been carried out to find new materials or mechanisms that optimize their performance and efficiency. Actually, the most used strategy consists of managing the scattering strength, for example, from the variation in the scattering particle density, or the excitation volume of the RL medium. This experimental procedure can also be used to tune the spatial coherence of RLs. , In a different approach, we recently demonstrated that by introducing a degree of randomness on the intensity distribution of the spatial light pattern that pumps a random lasing medium, it is possible to control and improve the RL efficiency by more than 1 order of magnitude .…”
Section: Introductionmentioning
confidence: 99%
“…The first three terms on the right describe the linear, quadratic, and cubic effective nonlinearities, respectively. For instance, phenomena such as second-harmonic generation and sum-frequency generation associated with were reported in RL experiments, due to self-induced second-order wave-mixing processes. , Moreover, variations in frequency and spatial localization of lasing modes, as well as laser intensity fluctuations, are attributed to the intensity-dependent refractive index associated with the third-order nonlinearity. , The third-order nonlinearity, associated with , also plays an important role in coupling the RL optical modes in a process leading to the replica symmetry-breaking phenomenon. …”
Section: Introductionmentioning
confidence: 99%